2023
DOI: 10.1073/pnas.2220012120
|View full text |Cite
|
Sign up to set email alerts
|

A macrocyclic peptide inhibitor traps MRP1 in a catalytically incompetent conformation

Abstract: Adenosine triphosphate-binding cassette (ABC) transporters, such as multidrug resistance protein 1 (MRP1), protect against cellular toxicity by exporting xenobiotic compounds across the plasma membrane. However, constitutive MRP1 function hinders drug delivery across the blood–brain barrier, and MRP1 overexpression in certain cancers leads to acquired multidrug resistance and chemotherapy failure. Small-molecule inhibitors have the potential to block substrate transport, but few show specificity for MRP1. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…We sorted the accessible PDB files for each protein by resolution, starting with higher-resolution structures and progressing to lowerresolution structures. 3.14 Å Cryo-EM 6UY0 [55] 3.23 Å Cryo-EM 8F4B [56] 3.27 Å Cryo-EM 5UJA [57] 3.34 Å Cryo-EM 5UJ9 [57] 3.49 Å Cryo-EM 7M68 [58] 4.04 Å Cryo-EM 3.30 Å X-ray 5KPD [60] 3.35 Å X-ray 4Q9H [61] 3.40 Å X-ray 6C0V [62] 3.40 Å Cryo-EM 5KPJ [59] 3.50 Å X-ray 4XWK [63] 3.50 Å X-ray 4Q9L [61] 3.80 Å X-ray 4M1M [64] 3.80 Å X-ray 5KOI [59] 3.85 Å X-ray 6UJN [65] 3.98 Å X-ray 5KPI [59] 4.01 Å X-ray Sav1866 2HYD [66] 3.00 Å X-ray 2ONJ [67] 3.40 Å X-ray MsbA 6BPL [68] 2.70 Å X-ray 6BPP [68] 2.92 Å X-ray 6BL6 [69] 2.80 Å X-ray 3B60 [70] 3.70 Å X-ray 5TV4 [71] 4.20 Å Cryo-EM 6UZL [72] 4. Each TMD (blue and red color) is composed of six transmembrane helices (1)(2)(3)(4)(5)(6).…”
Section: Abc Transportermentioning
confidence: 99%
“…We sorted the accessible PDB files for each protein by resolution, starting with higher-resolution structures and progressing to lowerresolution structures. 3.14 Å Cryo-EM 6UY0 [55] 3.23 Å Cryo-EM 8F4B [56] 3.27 Å Cryo-EM 5UJA [57] 3.34 Å Cryo-EM 5UJ9 [57] 3.49 Å Cryo-EM 7M68 [58] 4.04 Å Cryo-EM 3.30 Å X-ray 5KPD [60] 3.35 Å X-ray 4Q9H [61] 3.40 Å X-ray 6C0V [62] 3.40 Å Cryo-EM 5KPJ [59] 3.50 Å X-ray 4XWK [63] 3.50 Å X-ray 4Q9L [61] 3.80 Å X-ray 4M1M [64] 3.80 Å X-ray 5KOI [59] 3.85 Å X-ray 6UJN [65] 3.98 Å X-ray 5KPI [59] 4.01 Å X-ray Sav1866 2HYD [66] 3.00 Å X-ray 2ONJ [67] 3.40 Å X-ray MsbA 6BPL [68] 2.70 Å X-ray 6BPP [68] 2.92 Å X-ray 6BL6 [69] 2.80 Å X-ray 3B60 [70] 3.70 Å X-ray 5TV4 [71] 4.20 Å Cryo-EM 6UZL [72] 4. Each TMD (blue and red color) is composed of six transmembrane helices (1)(2)(3)(4)(5)(6).…”
Section: Abc Transportermentioning
confidence: 99%
“…While high-resolution cryo-EM structures have been determined for MRP1 only in the monomeric state, [16][17][18][19] studies of purified protein samples and studies in living cells indicate that MRP1 can also dimerize. 10,42,44,53 The dimerization interface of MRP1 has been proposed to involve TMD0, 10 and specifically that TM5 and the preceding extracellular loop (or loop-4 as defined in Fig.…”
Section: Ycf1p Dimer Structure Is Consistent With Predicted Dimers Of...mentioning
confidence: 99%
“…8b), the phosphorylation state P-glycoprotein can differ in different oligomeric states. 40 However, as with MRP1 [16][17][18][19] and CFTR [70][71][72][73]80,81 , high resolution structures have been determined only for monomeric states of ABCA1 82,83 , ABCA3 60 , P-glycoprotein, 84,85 and the dimeric form of the half transporter ABCG2. 86 The lack of dimeric structures for these ABC transporters, for which oligomerization has been detected biochemically, further suggests that oligomerization is transient or that the oligomeric state is unstable.…”
Section: Oligomerization Interfaces Vary Between Different Classes Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Numerous studies aiming to expand the genetic code have demonstrated the remarkable flexibility of flexizymes in selectively incorporating a diverse range of amino acids, including a, b, g, D and N-alkylated amino acids, hydroxy acids, nonamino carboxylic acids, peptides, and even foldamers. 3,[13][14][15] This groundbreaking method of intentionally misacylating tRNAs for the manipulation and reassignment of the genetic code with high fidelity and efficiency has greatly accelerated in vitro evolution, leading to advancements in mRNA display, 16 mirror-image translation, 17 and the development of novel cyclic peptide drug discovery, 16,[18][19][20] inhibitor selection, [21][22][23][24][25] polymerases, 26 and functional polymers. 27 Extensive exploration of RNA modifications has revealed their potential applications in gene expression, drug discovery, and clinical therapeutics.…”
mentioning
confidence: 99%